Identification of three phase IPM machine parameters using torque tests - Odhano, S.A.; Bojoi, R.I.; Armando, E.; Homrich, Guilherme; Filho, Aly Ferreira Flores; Popescu, Mircea; Dorrell, D.G. (IEEE, 2016)
This work presents a simple method for obtaining the main parameters, such as the torque constant and the d- and q-axis inductances Ld and Lq, for a brushless internal permanent magnet motor by measuring the machine torque during testing. These tests are relatively simple to carry out compared to other test procedures described in the literature and do not require sophisticated and expensive test equipment nor they are affected by temperature effects as happens with other techniques. The machine under test is supplied through a dc supply at different rotor positions. The shaft torque is measured through a torque sensor during the tests. The test current magnitude is varied to take care of the saturation effects. From the measured torque data and known rotor position, the required parameters can be obtained. Tests performed on two different internal permanent magnet machines confirm the validity and effectiveness of the proposed method.